Neurologic Recovery Following Prolonged Out-of-Hospital Cardiac Arrest With Resuscitation Guided by Continuous Capnography - White, Roger D. (Mayo Foundation for Medical Education and Research, 2011)
A 54-year-old man with no known cardiac disease collapsed outdoors in a small rural community. The cardiac arrest was witnessed, and immediate cardiopulmonary resuscitation was begun by a bystander and a trained first responder who was nearby. The patient was moved into a building across the street for continued resuscitation. First responders arrived with an automated external defibrillator, and ventricular fibrillation was documented. First responders delivered 6 defibrillation shocks, 4 of which transiently restored an organized electrocardiographic rhythm but with no pulse at any time. Additional emergency medical services personnel from nearby communities and an advanced life support (ALS) flight crew arrived. The flight crew initiated ALS care. The trachea was intubated, ventilation controlled, and end-tidal carbon dioxide tension continuously monitored. Antiarrhythmic and inotropic drugs were administered intravenously. An additional 6 shocks were delivered using the ALS defibrillator. End-tidal carbon dioxide measurements confirmed good pulmonary blood flow with chest compressions, and resuscitation was continued until a stable cardiac rhythm was restored after 96 minutes of pulselessness. The patient was transported by helicopter to the hospital. He was in cardiogenic shock but maintained a spontaneous circulation. Coronary angiography confirmed a left anterior descending coronary artery thrombotic occlusion that was treated successfully. After hospital admission, the patient required circulatory and ventilatory support and hemodialysis for acute renal failure. He experienced a complete neurologic recovery to his pre-cardiac arrest state. To our knowledge, this is the longest duration of pulselessness in an out-of-hospital arrest with a good outcome. Good pulmonary blood flow was documented throughout by end-tidal carbon dioxide measurements.